Revision of Tyroborus Oudemans, 1924 (Acari: Astigmata: Acaridae) - Fan, Qing-Hai; Zhang, Zhi-Qiang (Zootaxa, 2006)
Tyroborus Oudemans is revised with new characters discovered to confirm the validity of the genus. The relationships between Tyroborus, Tyrophagus and Tyrolichus are discussed. The type species of Tyroborus, T. lini Oudemans, is redescribed. Tyrophagus miripes Athias-Henriot is transferred to Tyroborus and redescribed. A new species, Tyroborus ueckermanni, is described from South Africa. A key to adults of the known species and data on habitats and distribution of each species are provided.